Magruder's american government 1998 - McClenaghan, William A. (Pearson Prentice Hall, 1998)
Magruder's American Government (1998) is a high school textbook that provides a comprehensive overview of the U.S. government. It covers the foundations of American democracy, the Constitution, the three branches of government (legislative, executive, and judicial), civil rights and liberties, political parties, elections, and the role of state and local governments. The book is designed to help students understand how the government works and encourages active citizenship. Magruder's American Government (1998) is a high school textbook that provides a comprehensive overview of the U.S. government. It covers the foundations of American democracy, the Constitution, the three branches of government (legislative, executive, and judicial), civil rights and liberties, political parties, elections, and the role of state and local governments. The book is designed to help students understand how the government works and encourages active citizenship.